E-051 Putting the "Eye" in I.V. Access—unconventional approaches in head and neck intervention. (4th July 2012) - Baxter, B; Mayich, M; Hungerford, J
Abstract : Introduction/purpose: Unconventional Access techniques have been documented in the literature and have the potential to provide a complimentary platform for intervention in select cases. This limited case series illustrates two such approaches. Materials/methods: Periprocedural clinical data and imaging was gathered around two cases requiring unconventional methods of access. Results: A 29-year-old female with known NF-1 was found to have a large dural AVF causing significant compression of the cervical cord. In the first stage of embolization, the right vertebral artery and thyrocervical perforating vessels providing antegrade flow to the lesion were occluded using a traditional femoral approach. Access to the left vertebral artery from the same approach was precluded by an aplastic proximal segment. Access to deploy coils and onyx to the distal right vertebral artery occluding retrograde filling was achieved by direct puncture of the artery near the skull base under fluoroscopic guidance. A 67-year-old female was diagnosed with a dural cavernous-carotid fistula after presenting with proptosis and conjuctival chemosis. Embolization of perforating branches from the external carotid by femoral approach was unsuccessful in occluding flow. Access was obtained by performing a limited cut down of the upper eyelid with ultrasound-guided catheterization the superior ophthalmic vein. Embolization of the cavernous sinus with coils and onyx resulted in immediate symptom resolution. Conclusion: In the absence of favorable access to a lesion by conventional femoral approach, unconventional access techniques may be safely employed for definitive treatment. Competing interests: B Baxter: Stryker Neurovascular, Penumbra, EV3, Codman, Rapid Medical, Reverse Medical. M Mayich: None. J Hungerford: None.